2016
DOI: 10.1016/j.jpedsurg.2015.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Development of an endoluminal intestinal attachment for a clinically applicable distraction enterogenesis device

Abstract: Purpose Previous methods of distraction enterogenesis have relied upon blind-ending intestinal segments or transmural device fixation, requiring multiple operations and potential bowel injury. We hypothesized that using a novel attachment would allow reversible device coupling to the luminal bowel surface, achieving effective endoluminal distraction. Methods A telescopic hydraulic device was designed with latex balloon attachments covered with high-friction mesh and a dilating fenestrated elastic mask (DFM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Recently, a variety of devices and operative approaches have been tested in animals for the treatment of SBS, but none of these approaches have been translated into clinical practice thus far. Self‐expanding, shape‐memory polymer cylinder, catheter device and a telescopic hydraulic device have all been tested, but their translations seem to be limited by the need for complex activation mechanisms or the surgical risks associated. These devices appeared challenging to use in a clinical scenario because of reported discomfort, pain and complications …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a variety of devices and operative approaches have been tested in animals for the treatment of SBS, but none of these approaches have been translated into clinical practice thus far. Self‐expanding, shape‐memory polymer cylinder, catheter device and a telescopic hydraulic device have all been tested, but their translations seem to be limited by the need for complex activation mechanisms or the surgical risks associated. These devices appeared challenging to use in a clinical scenario because of reported discomfort, pain and complications …”
Section: Discussionmentioning
confidence: 99%
“…To address this lack of dilatation recent studies on intestinal intraluminal devices have been proposed for the treatment of SBS, but currently their translation to clinical practice seems to be limited. Interestingly, the use of different devices as osmotic expanders have been popularized to increase the surface of several tissues such as; skin, soft tissue, or hypospadias cripples and has become the treatment of choice for many congenital and acquired defects; however, this technique has never been used to expand intestinal segments thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Demerhi et al . showed that a novel device using hydraulic force to apply distraction can reliably lengthen porcine bowel in experimental settings [2830]. This relied on a system where two balloons were placed within the bowel, which could be inflated to oppose the intestinal wall, and hydraulic distractive force was instilled in between these to achieve lengthening.…”
Section: Biongineeringmentioning
confidence: 99%
“…Our laboratory demonstrated effective intestinal lengthening using spring-mediated distractive devices [ 15 21 ]. However, these models are limited by multiple surgeries to repeat intestinal lengthening, restore intestinal continuity, or require extraluminal attachments [ 15 , 18 , 20 , 22 23 ].…”
Section: Introductionmentioning
confidence: 99%